Outcome measures for adults with Down Syndrome based on the International Classification of Functioning, Disability, and Health Model: A Systematic Review - Andrade, Michele Lacerda de; Silva , Soraia Micaela; Pereira, Gabriela Santos; Moraes, Janaina Ferreira de; Fonseca Junior, Paulo Roberto; Corrêa, João Carlos Ferrari; Corrêa, Fernanda Ishida (ABCS Health Sciences, 2023)
Introduction: Adults with Down syndrome (DS) have functional disabilities due to the extra presence of chromosome 21. Objective: To identify the functionality and disability assessment instruments used in research involving adults with DS and associate them with the components of the International Classification of Functioning (ICF). Methods: Two independent researchers analyzed articles from PubMed, Lilacs, SciELO, Science Direct, and Cochrane databases, including cross-sectional and clinical studies whose results involved functionality and disability for individuals with DS (≥18 years), with no publication date limit for the studies. The methodological quality of the studies was analyzed by the Downs & Black Checklist; descriptive analysis was used for the results. This review was registered in PROSPERO (CRD42021234012). Results: 15 articles were analyzed in which 48 instruments were identified for the assessment of adults with DS (36.42±10.62 years); the quality of the articles was considered "good". Of these 48 instruments, 41 were associated with bodily function, 5 instruments were associated with the activity component, one instrument was associated with social participation and one instrument was associated with the environment. Conclusion: Of the 48 instruments identified to assess adults with DS, most were for the Body Function and Structure component; only the 6MWT and CAMDEX-SD have been validated for this population. LIFE-H and MQE were used to assess Social Participation and the Environment, but they cannot be considered dependable, as they have not been confirmed for individuals with DS.